Analysis of work environment, discipline and ability of teachers at SMAN 3 Pontianak - Pelealu, Deasy Rinayanti (Junal Ilmu Manajemen, 2024)
This study investigates the impact of the work environment, work discipline, and work ability on teacher performance using multiple linear regression analysis. The regression model reveals that, in the absence of influence from these variables, the predicted teacher performance score is 64.376. The analysis indicates that while work discipline (β = 0.188) and work ability (β = 0.111) positively influence performance, the work environment (β = -0.484) has a negative impact. Correlation coefficient analysis shows that the work environment has a low and negative correlation with teacher performance (r = -0.335), whereas work discipline (r = 0.181) and work ability (r = 0.212) have very low to low positive correlations. The coefficient of determination (R² = 0.176) suggests that only 17.6% of the variation in teacher performance is explained by these variables, indicating that 82.4% of the variance is due to other unexamined factors. These findings highlight the complexity of factors affecting teacher performance and suggest the need for further research to explore additional influential variables.